The Correlation of Erythrocytosis Familial 6 (ECYT6) Gene Expression and their Targeted miRNA in Patients with Beta-Thalassemia - Al-kafagi, Hiba M. A.; Hussein, Lubna F.; Mohammed, Maryam Q.; Sulaiman, Ghassan M. (Iraqi Journal of Science, 2026)
Beta thalassemia is a genetic blood disorder that affects around 1.5% of the world's population. Beta globin, an essential component of hemoglobin, is involved in the development of this disease. The HBB gene, also known as the hemoglobin subunit beta gene, has been the focus of extensive studies, considering its crucial role in the production of hemoglobin. The associations between the HBB gene and various miRNA (miRNA) that serve as essential regulators of gene expression have been the subject of many investigations. In the current investigation, many blood indicators of thalassemia were assessed, RNA was extracted, cDNA was created, and quantitative real-time PCR was used to measure the expression of the HBB gene and miR-361-3p. The results showed a significant increase in the levels of ferritin and WBC in the patient group with a high significant difference (P≤ 0.01), while the HB value decreased in the patients with a high significant difference. Molecular results showed an increase in the gene expression level of the HBB gene with a value of (1.909) while a decrease in the gene expression level of the micro gene in thalassemia patients compared to the control group with a value of (0.692). The findings demonstrate that the downregulation of miR-361-3p results in an upregulation of its target genes, including HBB, leading to impaired erythropoiesis and abnormal red blood cell morphology, which are consistent with the pathophysiology of β-thalassemia. Consequently, it can be inferred that miR-361-3p plays a critical regulatory role in the pathogenesis of β-thalassemia by modulating HBB gene expression. The current study is limited by its small sample size, focus on a specific age group and single target gene. Future studies with a broader scope are recommended to overcome these limitations.